Diversity for development: the new strategy of the International Plant Genetic Resources Institute - International Plant Genetic Resources Institute; European Cooperative Programme for Plant Genetic Resources (1999)
In 1993, IPGRI published its first strategy as a new institute. The original Diversity for Development was written in the context of a world that had only come to grips with the connection between environment and development. The strategy described IPGRI's intention to concern itself primarily with what was, at that time, seen as one of the world's highest development priorities: the conservation of plant genetic resources for food and agriculture. It was impossible to predict in 1993 just how quickly things would change in the field of plant genetic conservation. It has led countries to re-examine their capacities to use, as well as to conserve, these resources. These international, national and institutional developments led IPGRI to re-examine and revise its strategy as the Institute prepared to celebrate its 25th anniversary in 1999. The outcome was a vision of the future that placed the use of genetic resources at the centre of rural development.